The Influence of Financial Literacy, Experience Regret and Mental Accounting on Student Investment Decisions at FEB UNRAM - Baiq Novina Windri Yatmi; Isnawati (Formosa Journal of Multidisciplinary Research, 2024)
This study aimed to assess the impact of financial literacy, regret aversion, and mental accounting on investment decisions among students at FEB UNRAM. The study focused on the population of actively enrolled students in the Faculty of Economics and Business, University of Mataram. The sample approach employed in this investigation was purposive sampling. The method of data analysis commences with the evaluation of the research instrument's validity and reliability, followed by the utilization of IBM SPSS Statistics for Windows 29 tools to conduct multiple regression tests and analyze the data. The findings indicate that financial literacy and mental accounting strongly influence student investment decisions at FEB UNRAM, but experience regret does not have any impact on these decisions.